COVID-19 and diabetes: A bidirectional relationship - Lima-Martínez, Marcos M; Carrera Boada, Carlos; Madera-Silva, Marialaura D; Marín, Waleskha; Contreras, Miguel (Clinica e investigacion en arteriosclerosis : publicacion oficial de la Sociedad Espanola de Arteriosclerosis, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causal agent of coronavirus disease 2019 (COVID-19). Diabetes is one of the most frequent comorbidities in people with COVID-19 with a prevalence that varies between 7 and 30%. Diabetics infected with SARS-CoV-2 have a higher rate of hospital admission, severe pneumonia, and higher mortality compared to non-diabetic subjects. Chronic hyperglycemia can compromise innate and humoral immunity. Furthermore, diabetes is associated with a low-grade chronic inflammatory state that favors the development of an exaggerated inflammatory response and therefore the appearance of acute respiratory distress syndrome. Recent evidence has shown that SARS-CoV-2 is also capable of causing direct damage to the pancreas that could worsen hyperglycemia and even induce the onset of diabetes in previously non-diabetic subjects. Therapeutic strategies should be aimed at facilitating patient access to the healthcare system. Control of blood glucose and comorbidities must be individualized in order to reduce the incidence of complications and decrease the burden on health systems. In this article we will review the pathophysiological mechanisms that explain the bidirectional relationship between COVID-19 and diabetes mellitus, its implication in the prognosis and management of hyperglycemia in this group of patients.